Biomimetic thiamine- and niacin-decorated liposomes for enhanced oral delivery of insulin - Haisheng He; Yi Lu; Jianping Qi; Weili Zhao; Xiaochun Dong; Wei Wu (Elsevier, 2018)
Biomimetic nanocarriers are emerging as efficient vehicles to facilitate dietary absorption of biomacromolecules. In this study, two vitamins, thiamine and niacin, are employed to decorate liposomes loaded with insulin, thus facilitating oral absorption via vitamin ligand-receptor interactions. Both vitamins are conjugated with stearamine, which works to anchor the ligands to the surface of liposomes. Liposomes prepared under optimum conditions have a mean particle size of 125-150 nm and an insulin entrapment efficiency of approximately 30%-36%. Encapsulation into liposomes helps to stabilize insulin due to improved resistance against enzymatic disruption, with 60% and 80% of the insulin left after 4 h when incubated in simulated gastric and intestinal fluids, respectively, whereas non-encapsulated insulin is broken down completely at 0.5 h. Preservation of insulin bioactivity against preparative stresses is validated by intra-peritoneal injection of insulin after release from various liposomes using the surfactant Triton X-100. In a diabetic rat model chemically induced by streptozotocin, both thiamine- and niacin-decorated liposomes showed a comparable and sustained mild hypoglycemic effect. The superiority of decorated liposomes over conventional liposomes highlights the contribution of vitamin ligands. It is concluded that decoration of liposomes with thiamine or niacin facilitates interactions with gastrointestinal vitamin receptors and thereby facilitates oral absorption of insulin-loaded liposomes.